The Effect Of The Discovery Learning Model On The Mathematics Learning Outcomes Of Grade V Students - Irawaty Mei Delila Damanik; Janwar Tambunan; Muktar B Panjaitan (PIJAR: Jurnal Pendidikan dan Pengajaran, 2026)
This study aims to determine the effect of the Discovery Learning model on the Mathematics learning outcomes of fifth-grade students of UPTD SD Negeri 122345 Pematangsiantar. This study uses a quantitative approach with an experimental method and a One-Group Pretest-Posttest Design. The research sample consisted of 25 students. The research instrument was a multiple-choice test of 20 questions that had met the validity and reliability tests with a Cronbach's Alpha value of 0.898 (very high). Data analysis used paired sample t-test and N-Gain test. The results showed that the average pretest score of 30.80 increased to 82.80 in the posttest. The calculated t-value of 49.960 was greater than the t-table of 2.064 with a significance of 0.000 <0.05. The N-Gain value of 0.76 was included in the high category. Thus, the Discovery Learning model had a significant and effective effect in improving students' Mathematics learning outcomes